Кооперативні банки як інструмент для фінансування аграрного сектору економіки - Добровольська, Олена Володимирівна; Dobrovolska, Olena (My University, 2017)
В статті розглянуто досвід розвитку кооперативних банків у світі. У світі кооперативні банки отримали розвиток в кризові періоди. Основна гіпотеза - розвиток малого бізнесу вимагає створення малих банків. Малому бізнесу потрібні кредитні спілки і кооперативні банки. The article discusses the experience of developing cooperative ones banks in the world. In the world, cooperative banks have developed in times of crisis. The basic hypothesis - the development of small business requires the creation of small ones banks Small businesses need credit unions and cooperative banks.
Cooperative banks as an instrument for financing the agrarian sector of the economy
Keywords: кооперативні банки; cooperative banks; фінансування; financing; аграрний сектор; agrarian sector; малий бізнес; small business